PENYELESAIAN SENGKETA KONSUMEN DI INDONESIA - Nur Amin, Muhammad; Liza Deshaini; Sudarna (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Abstract Settlement of consumer disputes in the General Courts is by filing lawsuits and examining evidence in court while settlement of consumer disputes outside the Court is by settlement of immediate (direct) compensation by peaceful means and claims for compensation through the Consumer Dispute Settlement Agency (BPSK). Keywords: Settlement, Dispute, Consumers